2013
DOI: 10.4095/292407
|View full text |Cite
|
Sign up to set email alerts
|

Geology, Stevenson Ridge (northeast part), Yukon

Abstract: The northeastern Stevenson Ridge map sheet (parts of NTS 115-J, I, P and O) is underlain by Paleozoic to Paleogene rocks that locally host Cu-Au porphyry and Au mineralization. The southwestern part of the area is dominated by the mid-Cretaceous Whitehorse plutonic suite which forms the backbone of the Dawson Range Mountains. The north side of the Dawson Range comprises rocks typical of the Yukon-Tanana terrane, including a belt of Permian Klondike schist (metavolcanic rocks), Permian Sulphur Creek plutonic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…75-74 Ma; Bennett et al 2009) that intrude Late Permian monzogranite orthogneiss, discontinuous lenses of serpentinized pyroxenite, and granitoids of the midCretaceous Dawson Range batholith (Bennett et al 2009;Ryan et al 2013; Yukon MINFILE 115J 008) (ESM 2).…”
Section: Geological Settingmentioning
confidence: 99%
“…75-74 Ma; Bennett et al 2009) that intrude Late Permian monzogranite orthogneiss, discontinuous lenses of serpentinized pyroxenite, and granitoids of the midCretaceous Dawson Range batholith (Bennett et al 2009;Ryan et al 2013; Yukon MINFILE 115J 008) (ESM 2).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Intermontane terranes, including Yukon‐Tanana terrane, were intruded by the Early Jurassic Aishihik suite (circa 186 Ma [ Johnston et al ., ]), within an extensive Mesozoic volcanic arc [ Logan and Mihalynuk , ], which consists of primarily coarse‐grained granodiorite to monzogranite [ Ryan et al ., , ]. Associated mineralization includes intrusion‐related and porphyry copper‐gold deposits [ Allan et al ., ].…”
Section: Geological and Metallogenic Evolution Of The Northern Canadimentioning
confidence: 99%
“…Ancient lithospheric lineaments, interpreted to be associated with long‐lived crustal structures, are important globally in their influence and control on subsequent tectonic deformation and faulting, crustal evolution, and the development of mineralization [e.g., Hildenbrand et al ., ; Chernicoff et al ., ; Hill et al ., ; Austin and Blenkinsop , , ; McMechan , ]. However, the use of geophysical and geological data in the investigation of regional geology and structure and in the exploration for mineral deposits in the northern Canadian Cordillera of Yukon‐eastern Alaska has primarily focused on the examination of upper crustal geology and structure [e.g., Hart et al ., ; Ryan et al ., , , ; Allan et al ., ; Nelson et al ., ; Sánchez et al ., , ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is commonly inferred on the basis of hornblende geobarometry and/or local geological relationships that many of the region's middle to Late Cretaceous plutons have not been significantly tilted since emplacement (e.g., Harris et al, , ; McCausland et al, ; Symons et al, , ; Symons & McCausland, ). For example, the Prospector Mountain stock (PM, Figure a) is inferred by Symons et al () to have not been tilted, but the intrusion is shown to be faulted along with the Late Cretaceous Carmacks Group volcanic rocks it intrudes (Ryan et al, ). Layered rocks of the Carmacks Group, present as outliers to the west of the Tintina fault, show a broad range of dips and azimuths both locally and regionally (e.g., Gordey & Ryan, ; Payne et al, ; Tempelman‐Kluit, , , ).…”
Section: Discussionmentioning
confidence: 99%
“…Late Cretaceous to Eocene magmatism was primarily focused in the Coast plutonic complex to the west (Nelson et al, ). However, intermediate to mafic volcanic and extrusive rocks of the Carmacks Group (circa 71–68 Ma, Grond et al, ; Joyce et al, ; Lowey et al, ; Smuk et al, ) and subvolcanic monzonitic intrusions of the Prospector Mountain suite (Ryan et al, ) represent a voluminous magmatic event of latest Cretaceous age in western Yukon. Low‐temperature (U‐Th)/He thermochronology from Neoproterozoic strata implies that regional compressional, associated with the Laramide deformation event (Aitken & Cook, ), resulted in shortening and uplift of the Mackenzie Mountains fold and thrust belt between the Albian (middle Cretaceous) and Paleocene (Powell, ; Powell et al, ).…”
Section: Tectonic Development Of the Northern Cordilleramentioning
confidence: 99%